Estimating national, regional and provincial cost-effectiveness of introducing childhood 13-valent pneumococcal conjugate vaccination in China: a modelling analysisResearch in context - Xiaozhen Lai; Cristina Garcia; Dan Wu; Maria Deloria Knoll; Haijun Zhang; Tingting Xu; Rize Jing; Zundong Yin; Brian Wahl; Hai Fang (Elsevier, 2023)
Summary: Background: Although 13-valent pneumococcal conjugate vaccine (PCV13) is available in China's private market, it has yet to be introduced into the National Immunization Programme (NIP) and is therefore not available to large parts of the population. This study aimed to estimate the cost-effectiveness of including PCV13 in China's NIP at national and provincial levels. Methods: We adopted a decision-tree Markov model to estimate the cost-effectiveness of adding 3-dose PCV13 in the NIP compared to the status quo in the private market from a societal perspective. The model hypothesized a birth cohort for five years after vaccine introduction. Treatment costs and vaccine program costs were calculated from Chinese Center for Disease Control and Prevention (CDC) and national insurance databases. Disease burden data, incidence rate ratios, and other parameters were derived from published and grey literature. Cases and deaths averted, quality-adjusted life years (QALYs) gained, and incremental cost-effectiveness ratios (ICERs) were estimated at the provincial, regional, and national levels. One-way, scenario and probabilistic sensitivity analyses were conducted to explore model uncertainty. Findings: At the national level, introducing PCV13 in the NIP was predicted to prevent approximately 4807 pneumococcal deaths (66% reduction) and 1,057,650 pneumococcal cases (17% reduction) in the first five years of the 2019 birth cohort. Under the assumed base case price of US$ 25 per dose in the NIP, PCV13 in the NIP was cost-effective nationally with ICER of US$ 5.222 per QALY gained, and was cost-effective in 17 and cost-saving in 4 of the 31 provinces compared to the status quo. One-way and scenario sensitivity analyses indicated robust results when varying all model parameters, and probabilistic sensitivity analysis showed a 98% probability of cost-effectiveness nationally. Interpretation: Our findings highlight the cost-effectiveness of introducing PCV13 in China's NIP. Provincial results supported subnational introduction of PCV13, and priority should be given to less socioeconomically developed provinces. Since vaccination cost is the most influential model parameter, efforts to improve PCV affordability after pooled procurement will benefit public health in a cost-effective manner. Funding: The Bill & Melinda Gates Foundation.